The Effect of Environmental Social and Governance (ESG) Business Strategy on Tax Aggressiveness with Corporate Social Responsibility (CSR) as a Moderation Variable - Rustandi Rustandi; Etty Murwaningsari (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
This study is designed to prove the influence of prospector and defender corporate strategy, environmental, social and governance (ESG) on tax aggressiveness with corporate social responsibility (CSR) as a moderation variable in Consumer Non-Cyclicals and Basic Material sector companies. Researchers studied samples of companies listed on the Indonesia Stock Exchange vulnerable 2019-2021 using purposive sampling techniques and obtained 74 companies as samples. This study analyzed the form of panel data with a random effect model approach. Companies that adopt both Prosfector and Defender business strategies have a direct influence on tax aggressiveness. However, companies with a Prosfector business strategy with corporate social responsibility (CSR) moderation can prolong their influence on tax aggressiveness, but companies with a Defender business strategy with corporate social responsibility (CSR) moderation can amplify their influence on tax aggressiveness. Aggressive tax reduction actions have an impact on the lack of sustainability of a company, stock prices that fall because the company's image becomes less favorable in the eyes of investors, because profits are recorded small. For the government, aggressive tax avoidance practices also bring losses because they have the opportunity to reduce state revenue from the tax sector. This finding provides strong evidence of the importance of information disclosure, especially in the company's sustainability aspect. This research contributes to understanding a company's tax behavior with its business strategy for developing countries.